“Our Modern Priapus”: Thauma and the Isernian Simulacra - Carter, Sarah (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2020)
In 1781, British Envoy Sir William Hamilton wrote to Joseph Banks of an astonishing discovery in rural Abruzzo. The inhabitants of Isernia offered wax phalluses as votives to Catholic shrines during the annual Fête of St. Cosmo and Damiano. The waxen vows were evidence that the cult of Priapus persisted in the modern world, and their appearance produced thauma or wonder in antiquarian circles. Moving from Hamilton’s letter to Richard Payne Knight’s A Discourse on the Worship of Priapus (1786), this essay draws from recent scholarship on the phenomenology of thauma to recast this well-known episode of the ex-voti as an eighteenth-century attempt to reconcile archaic Greek and modern modes of perception. Using archaic texts to ascribe new meaning to phallic emblems, Knight created an interpretative framework through which moderns might draw closer to the ancient world.